2021
DOI: 10.5312/wjo.v12.i8.575
|View full text |Cite
|
Sign up to set email alerts
|

Limb lengthening with PRECICE magnetic nail in pediatric patients: A systematic review

Abstract: BACKGROUND Limb lengthening techniques play an increasingly important role in the pediatric orthopedic field. The principles of the osteogenesis distraction bonded traditionally with external fixators; however, the recent deployment of fully implantable systems has been able to overcome severities related to external fixators. The PRECICE ® is an implantable limb lengthening intramedullary nail system that is remotely controlled and magnetically driven. AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In this study, the median distraction index was 1.0 mm/day (IQR 0.9-1.0). Previous studies have found similar distraction indices ranging from 0.7 to 0.9 mm/day [17,18,23,25]. Interestingly, the median consolidation index in this study of 20 days/cm (IQR [17][18][19][20][21][22][23] [12,16,18,19,23,26].…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the median distraction index was 1.0 mm/day (IQR 0.9-1.0). Previous studies have found similar distraction indices ranging from 0.7 to 0.9 mm/day [17,18,23,25]. Interestingly, the median consolidation index in this study of 20 days/cm (IQR [17][18][19][20][21][22][23] [12,16,18,19,23,26].…”
Section: Discussionsupporting
confidence: 72%
“…Antegrade femoral nails might be used in skeletally immature patients by using a trochanteric entry point; however, the age limit for avoiding avascular necrosis of the femoral head is unknown. A systematic review 19 of five studies 13,14,[20][21][22] with 131 patients ranging from 7 to 18 years of age did not report radiographic nor clinical signs of femoral head necrosis when using the trochanteric entry in 135 femoral lengthenings. In very young patients, off-label extramedullary use of the lengthening nails has allowed for internal femoral lengthening in patients as young as 4 years of age.…”
Section: Internal Nail Lengtheningmentioning
confidence: 99%
“…The internal actuator is activated by an external remote controller containing two neodymium magnets which control the distraction rate ( 34 , 37 ). In the pediatric population, this device has a reported mean lengthening range of 4.4–5.6 cm with nail accuracy (i.e., ratio of actual lengthening to planned lengthening) ranging from 91%–96% ( 38 ). While this device's use of the magnetic driving technique proves to be a feasible alternative to current motorized non-magnetic systems for the treatment of limb length discrepancy, limitations include device complications requiring surgical intervention (e.g., joint subluxation, delayed regenerate union, infection, nail fracture) and a wide variation in time to full weight bearing (range 21–132 days) ( 37 40 ).…”
Section: Magnetic Surgery For Musculoskeletal Disordersmentioning
confidence: 99%